Republic of Yemen Country Water Resources Assistance Strategy - World Bank (Washington, DC, 2012)
This note contains a summary, for practitioners, of the World Bank report Republic of Yemen country Water Resources Assistance Strategy (CWRAS). The preparation of a CWRAS is timely, given the rising pressure placed on water resources by the rapidly growing population and the emergence of lessons learned from a recent review of World Bank water projects in Yemen. This section reviews the current situation in Yemen, focusing on the following five key challenges facing the water sector: (i) over-extraction of groundwater; (ii) equitable and efficient valuation and allocation of water; (iii) meeting the millennium development goals (MDG) in potable water and sanitation; (iv) the need to protect water sources and the quality of water; and (v) building institutional capacity in the public sector.